218k views
4 votes
If f(x) = 2x2 + 1 and g(x) = x2 - 7, find (f + g)(x).​

User Surajd
by
5.9k points

1 Answer

5 votes

Answer:

(f+g)(x) =
3x^(2) - 6

Explanation:

First, lets understand what (f+g)(x) means.

(f+g)(x) is when you are taking the values in the function f(x) and adding it to the values in the function g(x).

So, this is what the equation looks like when you substitute the functions in to (f+g)(x):

(f+g)(x) =
(2x^(2) +1) + (x^(2) -7)

Now, combine like terms and Simplify:

(f+g)(x) =
3x^(2) - 6

This is your final answer.

User Dmitry Dyachkov
by
5.5k points